1990
DOI: 10.1007/bf00008888
|View full text |Cite
|
Sign up to set email alerts
|

Growth, biomass, mortality, production and potential yield of the West African clam, Egeria radiata (Lamarck) (Lamellibranchia, Donacidae) in the Cross River system, Nigeria

Abstract: An important fishery for the West African hemi-estuarine clam, Egeria radiata exists in the lower reaches of the Cross River (CR) system. The stock is heavily exploited but its productivity and potential yield have not been studied. This paper discusses the distribution and ecology of, and presents data on growth, abundance, mortality, biological production and potential yield of the CR stock of E. radiata based principally on length structured relative age. Growth was exponential and conformed to the von Bert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
(15 reference statements)
2
23
2
Order By: Relevance
“…It was, however, lower than the 145.1 mm obtained by Vakily (1992) from the re-analysed data collected by Kwei (1965) at an upstream station (Akosombo) on the Volta River and the 111.0 mm obtained by King et al (1992) on the Cross River stock of G. paradoxa. The L ∞ estimate in this study was higher than that of Moses (1990) and Etim and Brey (1994) for G. paradoxa stocks in the Cross River in Nigeria (Table II). The growth coefficient (K) estimate of 0.14-0.18 year −1 in this study was the lowest ever recorded in studies of the population dynamics of G. paradoxa (Table II).…”
Section: > Population Parameterscontrasting
confidence: 75%
See 1 more Smart Citation
“…It was, however, lower than the 145.1 mm obtained by Vakily (1992) from the re-analysed data collected by Kwei (1965) at an upstream station (Akosombo) on the Volta River and the 111.0 mm obtained by King et al (1992) on the Cross River stock of G. paradoxa. The L ∞ estimate in this study was higher than that of Moses (1990) and Etim and Brey (1994) for G. paradoxa stocks in the Cross River in Nigeria (Table II). The growth coefficient (K) estimate of 0.14-0.18 year −1 in this study was the lowest ever recorded in studies of the population dynamics of G. paradoxa (Table II).…”
Section: > Population Parameterscontrasting
confidence: 75%
“…It is endemic to the West African sub-region with a range that extends from the Gulf of Guinea to the Congo (Moses, 1990). Galatea Paradoxa is the basis of an artisanal clam fishery at the Volta River estuary providing employment and an affordable protein source to the riparian human communities and beyond (Amador, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is a filter-feeding organism with a wide distribution extending from the Gulf of Guinea to the Congo [10]. Limited information about the prevalence and commercial exploitation of this clam is available from only a few countries, including Ghana, Nigeria and Cameroon, despite its extensive distribution in the wider West African region [11].…”
Section: Study Speciesmentioning
confidence: 99%
“…In the present study, the value reported for L ∞ (14.75 cm) was higher than for other freshwater mussels. The lowest value (9.3 cm) was reported for the freshwater clam G. paradoxa (Donacidae: Veneroida) in the Cross River system in Nigeria (Moses, 1990). In the genus Crassostrea, the highest value (20.88 cm) was reported f or C. madrasensis (Amin et al, 2008) and was 1.5 times higher than that for E. elliptica.…”
Section: Figure 11 Relative Yield Per Recruit (Y /R) and Biomass Per mentioning
confidence: 96%
“…Therefore, urgent strategies are required for stock management, such as imposing a minimum landing size on fishermen (Adjei-Boateng and Wilson, 2012). Previously, Moses (1990) reported overexploitation of the freshwater clam G. paradoxa in Cross River in Nigeria with an exploitation ratio (E = 0.60) higher than the optimum value (E = 0.5) according to Gulland (1971). Overfishing was mainly due to juvenile exploitation.…”
Section: Introductionmentioning
confidence: 93%